2012
DOI: 10.1155/2012/606172
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregation of Huntingtin and α-Synuclein

Abstract: Huntington's and Parkinson's diseases are neurodegenerative disorders associated with unusual protein interactions. Although the origin and evolution of these diseases are completely different, characteristic deposits of protein aggregates (huntingtin and α-synuclein resp.), are a common feature in both diseases. After these observations, many studies are performed with both proteins. Some of them try to understand the nature and driving forces of the aggregation process; others try to find a correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 94 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Consequently, one can expect diverse kinds and levels of failure of protein homeostasis in different cell and tissue types. To further complicate the landscape of deficient protein homeostasis in the whole organism stands the diversity of possible substrates for CCT, which include a variety of proteins: structural ( Yam et al, 2008 ), regulatory of cell cycle and apoptosis ( Willison, 2018a ; 2018b ), and others involved in neural tissue development and degeneration ( Chánez-Cárdenas and Vázquez-Contreras, 2012 ). Substrate selection and binding depend on specific amino acid sequences on the client protein ( Willison, 2018a ; 2018b ) and on the translational context ( Yam et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, one can expect diverse kinds and levels of failure of protein homeostasis in different cell and tissue types. To further complicate the landscape of deficient protein homeostasis in the whole organism stands the diversity of possible substrates for CCT, which include a variety of proteins: structural ( Yam et al, 2008 ), regulatory of cell cycle and apoptosis ( Willison, 2018a ; 2018b ), and others involved in neural tissue development and degeneration ( Chánez-Cárdenas and Vázquez-Contreras, 2012 ). Substrate selection and binding depend on specific amino acid sequences on the client protein ( Willison, 2018a ; 2018b ) and on the translational context ( Yam et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant httex1-72Q protein fragments have been shown to form cytoplasmic aggregates and toxicity in vitro in the ST14A cells [13]. In R6/2 and httQ150 transgenic mice brains, with the progression of the disease, the aggregates were shown to become bigger, and functional deficits appeared after the presence of the aggregates [41, 42]. These data indicated the aggregating mhttex1-72Q, as seen in structures referred to here as foci, may be the cause of cellular toxicity in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Huntingtin (Htt), a hallmark protein of Huntington’s disease, has been observed to cross-seed and promote the fibrillation of TIA-1, an RNA-binding protein rich in glutamine and asparagine residues [ 202 ]. Another study found the occurrence of polyQ inclusions along with α-syn in samples of brain collected from HD rat models [ 203 , 204 ]. Aβ aggregation was influenced by cross-seeding with unrelated proteins that share a homologous aggregation-prone segment [ 205 ].…”
Section: Cross-seeding Of Amyloid Proteins: Role and Mechanismmentioning
confidence: 99%